Preparation method and application of hybrid material for identity card sheet
By blending PETG with PMMA and using titanate catalyst and sol-gel method to form compatibilizer and composite particles, the problem of poor compatibility of hybrid materials is solved, and the toughness, strength and compatibility of the material is achieved, and high-performance hybrid materials for ID card sheets are prepared.
Patent Information
- Application Number
- CN202411965636.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
The existing hybrid materials have poor compatibility, resulting in a decrease in strength when blended with PETG and PMMA, making it difficult to meet the toughness and strength requirements of ID card sheets.
The compatibility and performance of the material are improved by blending PETG with PMMA and using a titanate catalyst to form a compatibilizer, and SiO2@TiO2 composite particles are formed in situ in combination with the sol-gel method.
The compatibility of SiO2@TiO2 composite particles and matrix resin is significantly improved, the toughness and strength of the material are enhanced, the problems of compatibility, toughness and strength are solved, and PMMA/PETG/SiO2@TiO2 hybrid materials with good comprehensive performance are prepared.
Smart Images

Figure CN119708737A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a preparation method and application of a hybrid material for identity card sheets. Background Art
[0002] The excellent weather resistance of polymethyl methacrylate (PMMA) can resist climate change and ultraviolet radiation to ensure the durability of the material. It also has good solvent resistance and abrasion resistance. Therefore, it has good long-term usability as an ID card sheet. At the same time, its excellent light transmittance is also expected to be used in the preparation of ID cards with high brightness requirements.
[0003] However, when PMMA sheets are used as ID cards, their toughness still does not meet the requirements, so it is necessary to toughen and modify them. PETG is a polyethylene terephthalate (PET) modified with ethylene glycol (EG). The introduction of additional ethylene glycol units in its chemical structure makes the molecular chain more flexible, thereby improving the toughness and processing properties of the material. Its impact toughness is 5-10 times that of PMMA, and it has excellent transparency and gloss. However, its wear resistance is poorer than other hard plastics and it is easily scratched. Blending it with PMMA can achieve complementary performance, but improving the compatibility of the two is an urgent problem to be solved.
[0004] Among the frequently reported PC / PETG alloys, PETG improves the shortcomings of PC, such as poor fluidity and prone to stress cracking, while improving PC's solvent resistance and significantly reducing material costs. However, due to the soft texture of PETG, this type of alloy often loses strength, which greatly limits its application range. In addition, in the preparation process of PETG and other hard polyester blends, most of them use low-strength components grafted with MAH or GMA as a compatibilizer, which further reduces the strength of the alloy. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method and application of a hybrid material for identity card sheets, aiming to solve the problem of poor compatibility of existing hybrid materials.
[0006] To achieve the above objectives, in a first aspect, the present invention provides a method for preparing a hybrid material for an ID card sheet, comprising the following steps:
[0007] Compatibilized masterbatch was prepared using PMMA, PETG and titanate catalyst;
[0008] A matrix resin alloy is prepared using PMMA, PETG, a precursor and a silane coupling agent mixture, an antioxidant, and an ultraviolet absorber;
[0009] The compatibilizer masterbatch and the matrix resin are mixed evenly and then extruded into the plasticizing section of the extruder, and a mixed solution of an organic solvent and ionized water is added dropwise, and the PMMA / PETG / SiO2@TiO2 hybrid material is obtained through granulation.
[0010] Among them, in “preparing a volume-extending masterbatch using PMMA, PETG and a titanate-based catalyst”, the mass ratio of the PMMA to the PETG is 60:40-40:60; the titanate catalyst is any one of tetramethyl carbonate, tetraethyl titanate, isopropyl titanate and tetrabutyl titanate, and the amount used is 5%-10% of the total amount of PMMA and PETG; the extrusion temperature is 200-230°C.
[0011] Among them, in “preparing a matrix resin alloy using PMMA, PETG, a mixture of a precursor and a silane coupling agent, an antioxidant and an ultraviolet absorber”, the mass ratio of the PMMA to the PETG is 90:10-80:20; the precursor is any one of methyl orthosilicate, ethyl orthosilicate and propyl orthosilicate; the silane coupling agent is any one of glycidyl trimethoxysilane and glycidyl triethoxysilane; the mass ratio of the precursor to the silane coupling agent is 90:10-80:20; the mass ratio of the precursor / silane coupling agent mixture to PMMA / PETG is 90:10-80:20; the mass ratio of the precursor / silane coupling agent mixture to the ... The mass ratio of the ETG matrix is 90:10-70:30; the antioxidant is any one of antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 626 and antioxidant B215, and the dosage is 0.4%-0.6% of the mass of the matrix resin; the ultraviolet absorber is any one of UV-0326, UV-0327, UV-0328, UV-1164, UV-1577, UV-0770 and UV-144, and the content is 0.1%-0.3% of the mass of the matrix resin; the extrusion temperature is 200-230°C.
[0012] Among them, in "mixing the compatibilizer masterbatch and the matrix resin evenly and then extruding them into the plasticizing section of the extruder, and adding a mixed solution of organic solvent and ionized water, and granulating to obtain PMMA / PETG / SiO2@TiO2 hybrid material", the mass ratio of the matrix resin to the compatibilizer masterbatch is 80:20-70:30, the organic solvent is any one of tetrahydrofuran, chloroform, acetone and dimethylformamide; the ratio of the organic solvent to the deionized water is 90:10-95:5; the dripping rate of the mixed solution is 2-4 drops per second; and the extrusion temperature is 200-230°C.
[0013] In the second aspect, an application of a hybrid material for an ID card sheet is applied to the method for preparing a hybrid material for an ID card sheet as described in any one of claims 1 to 4, comprising thoroughly drying the prepared hybrid material and then extruding it into a sheet; the temperatures of each section of the extruder are 180°C, 190°C, 210°C, 210°C, 220°C, 220°C, 230°C, 230°C, and 220°C, respectively, and the rotation speed is 230r / min.
[0014] The preparation method of any hybrid material for ID card sheet of the present invention comprises the following steps: using PMMA, PETG and titanate catalyst to prepare compatibilizer masterbatch; using PMMA, PETG, precursor and silane coupling agent mixture, antioxidant and ultraviolet absorber to prepare matrix resin alloy; mixing the compatibilizer masterbatch and matrix resin uniformly, extruding the plasticizing section of the extruder, and dripping the mixed solution of organic solvent and ionized water, and granulating to obtain PMMA / PETG / SiO2@TiO2 hybrid material. The present invention, by blending PETG with PMMA, the alloy with excellent comprehensive performance can better overcome the problems of PMMA brittleness and easy cracking. On the other hand, the presence of PMMA can provide better optical properties. The compatibilizer is formed by titanate-catalyzed ester exchange of PETG and PMMA side chains, and SiO2@TiO2 composite particles are formed in situ by sol-gel method. The cyclosilane coupling agent is used to participate in the sol-gel reaction and epoxy compatibilization reaction at the same time, which significantly improves the compatibility of SiO2@TiO2 composite particles and matrix resin. While PETG toughens PMMA, SiO2@TiO2 composite particles are used for reinforcement, achieving compatibility, toughness and strength. PMMA / PETG / SiO2@TiO2 hybrid materials with good comprehensive performance are prepared. This solves the problem of poor compatibility of existing hybrid materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0016] Figure 1 It is a flow chart of a method for preparing any hybrid material for identity card sheet provided by the present invention. DETAILED DESCRIPTION
[0017] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0018] See also Figure 1 In a first aspect, the present invention provides a method for preparing a hybrid material for an identity card sheet, comprising the following steps:
[0019] S1 uses PMMA, PETG and titanate catalyst to prepare compatibilized masterbatch;
[0020] The mass ratio of the PMMA to the PETG is 60:40-40:60; the titanate catalyst is any one of tetramethyl carbonate, tetraethyl titanate, isopropyl titanate and tetrabutyl titanate, and the amount used is 5%-10% of the total amount of PMMA and PETG; the extrusion temperature is 200-230°C.
[0021] Specifically, a certain proportion of PMMA, PETG and a titanate catalyst are uniformly mixed in a high-speed mixer, and then the mixture is subjected to reaction extrusion granulation in a twin-screw extruder.
[0022] S2 uses PMMA, PETG, a mixture of a precursor and a silane coupling agent, an antioxidant, and an ultraviolet absorber to prepare a matrix resin alloy;
[0023] The mass ratio of PMMA to PETG is 90:10-80:20; the precursor is any one of methyl orthosilicate, ethyl orthosilicate, and propyl orthosilicate; the silane coupling agent is any one of epoxypropyl trimethoxysilane and epoxypropyl triethoxysilane; the mass ratio of the precursor to the silane coupling agent is 90:10-80:20; the mass ratio of the precursor / silane coupling agent mixture to the PMMA / PETG matrix is 90:10-70:30; the antioxidant The antioxidant is any one of antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 626 and antioxidant B215, and the dosage is 0.4%-0.6% of the mass of the base resin; the ultraviolet absorber is any one of UV-0326, UV-0327, UV-0328, UV-1164, UV-1577, UV-0770 and UV-144, and the content is 0.1%-0.3% of the mass of the base resin; the extrusion temperature is 200-230°C.
[0024] Specifically, PMMA, PETG, a mixture of a precursor and a silane coupling agent, an antioxidant and an ultraviolet absorber are fully and uniformly mixed by a high-speed mixer according to a certain proportion, and granulated by a twin-screw extruder.
[0025] S3: the compatibilizer masterbatch and the matrix resin are mixed evenly and then extruded into the plasticizing section of the extruder, and a mixed solution of an organic solvent and ionized water is added dropwise, and a PMMA / PETG / SiO2@TiO2 hybrid material is obtained through granulation.
[0026] The mass ratio of the base resin to the compatibilizing masterbatch is 80:20-70:30, the organic solvent is any one of tetrahydrofuran, chloroform, acetone and dimethylformamide; the ratio of the organic solvent to the deionized water is 90:10-95:5; the dripping rate of the mixed solution is 2-4 drops per second; and the extrusion temperature is 200-230°C.
[0027] Specifically, the compatibilizer masterbatch and the matrix resin are uniformly mixed in a high-speed mixer in a certain ratio, a mixed solution of an appropriate amount of organic solvent and ionized water is dripped into the plasticizing section of the twin-screw extruder, and the PMMA / PETG / SiO2@TiO2 hybrid material is obtained by extrusion granulation, and then extruded into sheets.
[0028] Example 1
[0029] (1) Preparation of compatibilized masterbatch: PMMA, PETG and tetrabutyl titanate in a mass ratio of 60:40:10 were mixed uniformly in a high-speed mixer, and then subjected to reactive extrusion granulation at 200-230° C. using a twin-screw extruder.
[0030] (2) Preparation of matrix resin alloy: PMMA and PETG in a mass ratio of 90:10 are uniformly mixed in a high-speed mixer, followed by adding a mixture of 10% of the mass of the matrix resin of tetraethyl orthosilicate / epoxypropyltrimethoxysilane, wherein the mass ratio of tetraethyl orthosilicate to epoxypropyltrimethoxysilane is 90:10, and then adding 0.4% of the mass of the matrix resin of antioxidant 1076 and 0.2% of the ultraviolet absorber UV-0326, and continuing to mix at a high speed, and finally granulating through a twin-screw extruder at an extrusion temperature of 200-230°C.
[0031] (3) Preparation of PMMA / PETG / SiO2@TiO2 hybrid material: The compatibilizer masterbatch and the matrix resin were mixed uniformly in a high-speed mixer at a mass ratio of 10:90, and granulated by a twin-screw extruder at an extruder temperature of 200-230°C. During the granulation process, a mixed solution of tetrahydrofuran / deionized water with a mass ratio of 90:10 was uniformly added at a rate of 2 drops per second in the plasticizing section of the twin-screw extruder.
[0032] Example 2
[0033] (1) Preparation of compatibilized masterbatch: PMMA, PETG and tetrabutyl titanate in a mass ratio of 60:40:8 were mixed uniformly in a high-speed mixer, and then subjected to reactive extrusion granulation at 200-230° C. using a twin-screw extruder.
[0034] (2) Preparation of matrix resin alloy: PMMA and PETG in a mass ratio of 85:15 are uniformly mixed in a high-speed mixer, followed by adding a mixture of 20% of the mass of the matrix resin of tetraethyl orthosilicate / epoxypropyltrimethoxysilane, wherein the mass ratio of tetraethyl orthosilicate to epoxypropyltrimethoxysilane is 80:20, and then adding 0.5% of the mass of the matrix resin of antioxidant 1010 and 0.3% of the ultraviolet absorber UV-1164, and continuing to mix at a high speed, and finally granulating through a twin-screw extruder at an extrusion temperature of 200-230°C.
[0035] (3) Preparation of PMMA / PETG / SiO2@TiO2 hybrid material: The compatibilizer masterbatch and the matrix resin were mixed uniformly in a high-speed mixer at a mass ratio of 15:85, and granulated by a twin-screw extruder at an extruder temperature of 200-230°C. During the granulation process, a mixed solution of tetrahydrofuran / deionized water with a mass ratio of 90:10 was uniformly added at a rate of 3 drops per second in the plasticizing section of the twin-screw extruder.
[0036] Example 3
[0037] (1) Preparation of compatibilized masterbatch: PMMA, PETG and tetrabutyl titanate in a mass ratio of 50:50:10 were mixed uniformly in a high-speed mixer, and then subjected to reactive extrusion granulation at 200-230° C. using a twin-screw extruder.
[0038] (2) Preparation of matrix resin alloy: PMMA and PETG in a mass ratio of 80:20 are uniformly mixed in a high-speed mixer, followed by adding a mixture of 30% of the mass of the matrix resin of tetraethyl orthosilicate / epoxypropyltrimethoxysilane, wherein the mass ratio of tetraethyl orthosilicate to epoxypropyltrimethoxysilane is 80:20, and then adding 0.6% of the mass of the matrix resin of antioxidant 1010 and 0.3% of the ultraviolet absorber UV-0328, and continuing to mix at a high speed, and finally granulating through a twin-screw extruder at an extrusion temperature of 200-230°C.
[0039] (3) Preparation of PMMA / PETG / SiO2@TiO2 hybrid material: The compatibilizer masterbatch and the matrix resin were mixed uniformly in a high-speed mixer at a mass ratio of 20:80, and granulated by a twin-screw extruder at an extruder temperature of 200-230°C. During the granulation process, a mixed solution of dimethylformamide / deionized water with a mass ratio of 90:10 was uniformly added at a rate of 4 drops per second in the plasticizing section of the twin-screw extruder.
[0040] Example 4
[0041] (1) Preparation of compatibilized masterbatch: PMMA, PETG and tetrabutyl titanate in a mass ratio of 60:40:10 were mixed uniformly in a high-speed mixer, and then subjected to reactive extrusion granulation at 200-230° C. using a twin-screw extruder.
[0042] (2) Preparation of matrix resin alloy: PMMA and PETG in a mass ratio of 90:10 are uniformly mixed in a high-speed mixer, followed by adding a mixture of 30% of the mass of the matrix resin of tetraethyl orthosilicate / epoxypropyltrimethoxysilane, wherein the mass ratio of tetraethyl orthosilicate to epoxypropyltrimethoxysilane is 90:10, and then adding 0.5% of the mass of the matrix resin of antioxidant 626 and 0.3% of the ultraviolet absorber UV-0770, and continuing to mix at a high speed, and finally granulating through a twin-screw extruder at an extrusion temperature of 200-230°C.
[0043] (3) Preparation of PMMA / PETG / SiO2@TiO2 hybrid material: The compatibilizer masterbatch and the matrix resin were mixed uniformly in a high-speed mixer at a mass ratio of 10:90, and granulated by a twin-screw extruder at an extruder temperature of 200-230°C. During the granulation process, a mixed solution of dimethylformamide / deionized water with a mass ratio of 95:5 was uniformly added at a rate of 3 drops per second in the plasticizing section of the twin-screw extruder.
[0044] Comparative Example 1
[0045] Pure PETG was injection molded into standard specimens for testing.
[0046] Comparative Example 2
[0047] Pure PMMA was injection molded into standard specimens for testing.
[0048] Comparative Example 3
[0049] PETG, PMMA, antioxidant and UV absorber were fully mixed in a high-speed mixer at a ratio of 7:3:0.2:0.5:0.1, and extruded and granulated by a twin-screw extruder to prepare the sample strip. The temperature of each temperature zone of the extruder was set to 180°C, 190°C, 210°C, 210°C, 220°C, 220°C, 230°C, 230°C, 220°C, and the speed was 230r / min.
[0050] Application performance testing
[0051] The hybrid materials and blended materials prepared in Examples 1-4 and Comparative Examples 1-3 were injection molded into standard specimens, and tensile and impact performance tests were performed according to GB / T 1040-2006 and GB / T 1843-2008, wherein the PETG brand was Eastman Tritan MN004 of Eastman Chemical of the United States, and the PMMA brand was Chimei CM-205. The test results are shown in Table 1.
[0052] Table 1 Mechanical properties
[0053]
[0054] From the above data, we can see that:
[0055] (1) Compared with Examples 1-3 and all the control examples, pure PETG has better toughness, but poorer strength and deformation resistance, while pure PMMA has higher strength but very poor toughness; after the two are directly blended, the toughness is slightly improved, but the strength loss is very large, indicating that the two are not compatible.
[0056] (2) Comparative Examples 1-3 show that as the content of the PETG component increases, the impact strength of the hybrid material increases, while the tensile strength, elongation at break and flexural modulus all increase gradually. The main reason for this is that, on the one hand, the toughening effect of PETG is obvious; while increasing the PETG content, the amount of precursor and silane coupling agent is increased, and the in-situ formed SiO2@TiO2 can effectively reinforce and improve the strength and deformation resistance of the material.
[0057] (3) In Comparative Examples 1 and 4, at the same PETG dosage, increasing the dosage of the precursor and the silane coupling agent will affect the material strength. This may be because the SiO2@TiO2 particles formed by the sol-gel process are too large, resulting in slight phase separation.
[0058] Beneficial effects of the present invention:
[0059] 1. In the present invention, PETG and PMMA are blended to produce an alloy with excellent comprehensive performance, which can better overcome the problems of PMMA such as high brittleness and easy cracking. On the other hand, the presence of PMMA can provide better optical properties.
[0060] 2. The present invention forms a compatibilizer by catalyzing the ester exchange of PETG and PMMA side chains through titanate, forms SiO2@TiO2 composite particles in situ by a sol-gel method, and combines a cyclosilane coupling agent to simultaneously participate in the sol-gel reaction and the epoxy group compatibilization reaction, thereby significantly improving the compatibility of the SiO2@TiO2 composite particles and the matrix resin. While PETG toughens PMMA, SiO2@TiO2 composite particles are used to reinforce it, thereby achieving a balance of compatibility, toughness and strength, and preparing a PMMA / PETG / SiO2@TiO2 hybrid material with good comprehensive performance.
[0061] The above disclosure is only a preferred embodiment of the preparation method and application of a hybrid material for an ID card sheet of the present invention. Of course, this cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiments and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.
Claims
1. A method for preparing a hybrid material for an ID card sheet, characterized in that: The following steps are involved: Compatibilized masterbatch was prepared using PMMA, PETG and titanate catalyst; A matrix resin alloy is prepared using PMMA, PETG, a precursor and a silane coupling agent mixture, an antioxidant, and an ultraviolet absorber; The compatibilizer masterbatch and the matrix resin are mixed evenly and then extruded into the plasticizing section of the extruder, and a mixed solution of an organic solvent and ionized water is added dropwise, and the PMMA / PETG / SiO2@TiO2 hybrid material is obtained through granulation.
2. The method for preparing the hybrid material for identity card sheet according to claim 1, characterized in that: In "Preparing a compatibilized masterbatch using PMMA, PETG and a titanate catalyst", the mass ratio of the PMMA to the PETG is 60:40-40:60; the titanate catalyst is any one of tetramethyl carbonate, tetraethyl titanate, isopropyl titanate and tetrabutyl titanate, and the amount used is 5%-10% of the total amount of PMMA and PETG; the extrusion temperature is 200-230°C.
3. The method for preparing the hybrid material for identity card sheet according to claim 1, characterized in that: In "preparing a matrix resin alloy using PMMA, PETG, a mixture of a precursor and a silane coupling agent, an antioxidant and an ultraviolet absorber", the mass ratio of the PMMA to the PETG is 90:10-80:20; the precursor is any one of methyl orthosilicate, ethyl orthosilicate and propyl orthosilicate; the silane coupling agent is any one of glycidyl trimethoxysilane and glycidyl triethoxysilane; the mass ratio of the precursor to the silane coupling agent is 90:10-80:20; the mass ratio of the precursor / silane coupling agent mixture to PMMA / PETG ... The mass ratio of G matrix is 90:10-70:30; the antioxidant is any one of antioxidant 1010, antioxidant 1076, antioxidant 168, antioxidant 626 and antioxidant B215, and the dosage is 0.4%-0.6% of the mass of the matrix resin; the ultraviolet absorber is any one of UV-0326, UV-0327, UV-0328, UV-1164, UV-1577, UV-0770 and UV-144, and the content is 0.1%-0.3% of the mass of the matrix resin; the extrusion temperature is 200-230°C.
4. The method for preparing the hybrid material for identity card sheet according to claim 1, characterized in that: In the step of "mixing the compatibilizer masterbatch and the matrix resin uniformly and then extruding them into a plasticizing section, and dropping a mixed solution of an organic solvent and ionized water, and granulating to obtain a PMMA / PETG / SiO2@TiO2 hybrid material", the mass ratio of the matrix resin to the compatibilizer masterbatch is 80:20-70:30, the organic solvent is any one of tetrahydrofuran, chloroform, acetone and dimethylformamide; the ratio of the organic solvent to the deionized water is 90:10-95:5; the dripping rate of the mixed solution is 2-4 drops per second; and the extrusion temperature is 200-230°C.
5. An application of a hybrid material for an ID card sheet, applied to the preparation method of the hybrid material for an ID card sheet according to any one of claims 1 to 4, characterized in that: The method includes thoroughly drying the prepared hybrid material and then extruding it into a sheet; the temperatures of each section of the extruder are 180°C, 190°C, 210°C, 210°C, 220°C, 220°C, 230°C, 230°C, and 220°C, and the rotation speed is 230r / min.